The haematology of Trypanosoma congolense infection in cattle. I. Sequential cytomorphological changes in the blood and bone marrow of Boran cattle - Anosa, V.O.; Logan-Henfrey, L.L.; Wells, C.W. (Springer, 1997)
Five adult Boran cattle (Bos indicus), infected with a clone of Trypanosoma congolense IL13-E3 three years earlier and treated, were re-challenged with the same clone. Changes in the peripheral blood were monitored twice weekly, and events in the bone marrow (BM) were assessed by weekly biopsies of the sternal BM, until day 98 postinfection (dpi) when the three surviving animals were treated with diminazene aceturate. One animal died on 57 dpi whereas another was treated on 63 dpi when the packed cell volume was 15 percent. The infected animals developed anaemia, leucopenia and thrombocytopenia during the first peak of parasitaemia which persisted until the experiment was terminated. Three phases of BM response were demonstrated on light microscopic examination of BM smears. The first, the preparasitaemic phase represented by samples taken on 15 dpi, was an immunological response with slight but significant increases in lymphoblasts, lymphocytes, plasma cells and macrophages (Mo) whereas erythroid and granulocytic cells were unchanged. The second, the early parasitaemic or acute phase (21-57 dpi) associated with the development of anaemia, leucopenia and thrombocytopenia, was characterised by intensification of the immunological response, and an early but transient granulocytic hyperplasia. The third, the late parasitaemic or chronic phase (63-98 dpi) associated with persisting pancytopenia, was characterised by erythroid, megakaryocytic and Mo hyperplasia, dyserythropoiesis, granulocyte hypoplasia and return of lymphoid cell counts to preinfection numbers. Transmission electron microscopy confirmed these findings and showed that intact trypanosomes were not observed in the sinusoids and haemopoietic compartment of the BM. This study demonstrates that T. congolense infection affects haemopoiesis, downregulating or upregulating the various blood cell lineages depending on the stage of infection. This suggests a fine control mechanism, presumably cytokine-mediated. Erythropoiesis, thrombopoiesis and monocytopoiesis were generally upregulated, whereas granulopoiesis was downregulated. However, haemopoiesis was generally ineffective as numbers of circulating blood cells remained below preinfection levels throughout the period of the study.